Determinants of educator job satisfaction in private higher education providers - Ting, Hui Bun (Universiti Malaysia Sarawak, (UNIMAS), 2010)
TIte purpose of this research is to identify potential factors that can contrib~te to educator job satisfaction in the context of private higher education providers ih Kuching, Sarawak. Questio~aire has been distributed to 5 private colleges in Kuchinv Results of questionnaire with 76 sample of educators indicated that internal motivators contribute more to job satisfaction, if compare to external motivators. There are six internal and 6 external motivators identified in this research. Descriptive, factor analysis, Pearson correlation and regression analysis were used in this study. In addition, limitation ofthe research and some recommendations for future research were made.